Studying Robots, between Science and the Humanities. - Kakoudaki, Despina (International Journal of the Humanities, 2007)
In this paper I explore the figure of the robot as an object of study, and one that specifically requires an integration of methodologies from both the humanities and the sciences. Traditionally, the figure of the robot has been regarded very differently in these two realms: in the sciences, it is related to the promises of scientific inquiry, and motivates research and innovation in actual technological applications, or the future possibility for such applications. In the humanities, however, the robot is a figure of fiction and science fiction, which, despite its un-reality channels feelings about culture and technology, difference and justice, often in indirect ways. After exploring the implications and fundamental trends of the two modes, the paper proposes that an integrated interdisciplinary methodology would allow us to better understand the attraction and meaning of the robot as a figure, without resorting to the binary opposition between fantasy and reality. Using examples from fiction, popular culture, recent scientific applications and research in robotics, I argue that the two approaches fuel each other: as cultural figures, robots are both real and imaginary, and indeed it is often their imaginary qualities that fuel and inspire actual research.